ISOLASI DAN UJI PENANGKAPAN RADIKAL BEBAS DPPH OLEH ISOLAT-1, FRAKSI ETIL ASETAT, DAN EKSTRAK ETANOL AKAR PASAK BUMI (Eurycoma longifolia Jack) - Nurani, Laela Hayu (Universitas Ahmad Dahlan, 2013)
The free radical was produced when undertaking processes metabolit or opposedinfection and when the body dissolved food. The unstable free radical could beneutralised with antioxidant. The root of the pasak bumi (Eurycoma longifolia Jack)was known contained the compound flavonoid, that it was known had the activity asantioxidant. This research aimed at knowing the activity capacity of the capture of thefree radical the water fraction and the faction ethyl acetate fraction the extract ethanolof the root of the pasak bumi by using the DPPH method.The root of the pasak bumi was extracted with ethanol 70% used maceration. Theethanolic extract was dissolved in ethyl acetate, fractination with ethyl acetate so as tobe received by the fraction ethyl acetate. The concentration of the ethanolic extract andthe fraction of ethyl acetate that was used were 2; 4; 8; 16 ug/mL and isolat-1 that is:0.8; 1.6; 3.2; and 6.4 ug/mL.Results of the research showed that all the treatments had the activity asscavenging the free radical. Results of the analysis statistika with the Kruskal Wallismethod in the level of the confident 95% that was followed by the test Mann Whitneyshowed the existence of the difference of the activity of the capture of the free radicalwho was significant between respectively the treatment group. The conclusion from thisresearch was the value ES50 ethanalic extract (15.64 ug/mL) bigger than the factionethyl acetate fraction and higher (13.948 ug/mL) value of ethanalic extract was thanisolat 1 (3.961 g/mL).